Assessing Hospital Management Information Systems Success Using Human Organization and Technology Fit Model - Devina Vantissha; Anik Hanifatul Azizah; Syamsul Arifin (Applied Information System and Management (AISM), 2022)
Arsani Hospital has implemented Hospital Management Information Systems since 2010 to support operations to improve services, work effectiveness, and efficiency. However, in its implementation, there are obstacles such as the seldom use of Hospital Management Information Systems and employees' lack of knowledge. Also, the appearance of Hospital Management Information Systems is challenging to understand, and Hospital Management Information System has not been integrated (BPJS system, attendance, and employee payroll). In addition, there are queues in the administrative process. To ensure Hospital Management Information Systems can achieve the expected targets, its necessary to evaluate the success of the implementation as quantitatively using the HOT-Fit (Human Organizational and Technology Fit) model. The model focuses on three dimensions, namely human (system development, user satisfaction, system use), organization (organizational structure, organizational environment), and technology (quality systems, information quality, service quality). This study aims to determine the factors that influence Hospital Management Information Systems implementation success rate at Arsani Hospital using a questionnaire. A total of l99 respondents were obtained by analyzing PLS-SEM data using SmartPLS v3.3 software. The results showed that of the 18 hypotheses developed, 11 were accepted, while the other seven were rejected. The output of this research is given several recommendations which are intended to increase the success rate of Hospital Management Information Systems at Arsani Hospital.